Local tectonic deformations measured by extensometer at the eastern foothills of the Alps at the Sopronbánfalva Geodynamic Observatory, Hungary - MENTES, Gyula; KISZELY, Márta (Contributions to Geophysics and Geodesy, 2019)
In Hungary, at the foot of the Eastern Alps, in the Sopronb´anfalva Geodynamic Observatory (SGO), a quartz-tube extensometer has been used for recording the Earth’s tides and local tectonic deformations since 1991. The 27-year long strain record (1991–2017) shows a continuous compression of the rock with changing rate. The relations between the measured local deformation and present-day tectonics in the region of the observatory were investigated. The local strain rate variations were also compared with the temporal and spatial distribution as well as with the magnitudes of earthquakes occurred within 200 km from the observatory in two sectors around the azimuth of the extensometer (116°): 116°±15° and 296°±15°. Our investigations show that earthquakes can also influence the strain rate. Earthquakes to the west of SGO generally increase the compressive strain rate, while earthquakes in the Pannonian Basin, with some exceptions, have no significant effect on the local strain rate variations measured in the SGO. It has been found that the recorded compressive strain is in good accordance with the recent tectonic processes in the region of the SGO determined by Global Navigation Satellite System (GNSS) technology and geophysical measurements. From the results it can be concluded that the uplift of the Alps, tectonic processes in the East Alpine region and in the Pannonian Basin play the most important role in the changing local compressive strain rate.